The Art of Customization: Text-to-Image Tools in Video Production - Wilson Wilson; Alfa Yohannis; Erick Dazki (TEPIAN, 2025)
As technology progresses, the need for tailored experiences is reshaping video editing, particularly due to the new content demands arising from social media. The advent of Artificial Intelligence (AI) has introduced significant advantages, such as enhanced workflow efficiency, cost reduction, and the generation of high-quality materials. However, professionals in the creative sector still express concerns about issues related to security, privacy, and the fear that AI might supplant human jobs. These worries, along with the potential loss of creative autonomy, can be mitigated through concise training that educates users on the capabilities of AI. By mastering these tools, creators can utilize AI to streamline their processes while preserving their artistic integrity. A comparison of various recently launched AI text-to-image applications reveals notable disparities in both accuracy and quality. Additionally, discussions with industry professionals indicate that those who have successfully incorporated AI into their workflows strongly endorse specific software that has significantly boosted their productivity. This suggests that, when implemented thoughtfully and with the right tool selection, AI can serve as a valuable resource in the realm of innovative and personalized video production